Combating physical inactivity : assessing physical activity patterns of Secondary school students in Singapore - Cho, Tessa Jin Jin (2017)
The purpose of this study was to identify the physical activity patterns of Secondary school students in Singapore using an objective measure. Previous research on the physical activity levels of adolescents in Singapore has reported alarmingly low engagement levels, despite the various efforts to increase physical inactivity. Hence, these findings can help identify aspects for interventions to focus on to increase physical activity effectively. A wrist-worn triaxial accelerometer was used to collect raw accelerometer data from 48 participants, aged between 13 to 15 years old, over 7 consecutive days. Separate mixed between-within subject analysis of variances were used to identify the main and interaction effects between different time periods of weekdays and weekends, and different genders or weight status, within moderate-to-vigorous physical activity in non-bout activity (MVPAnonbout) and MVPA in bouts of 10 minutes or more (MVPA10mins), respectively. Results from the study found that the amount of physical activity done on weekends was significantly lesser than that on weekdays. A significant main effect for the mean amount of time spent in MVPAnonbout over the different time periods with different genders (p < .001) and weight status (p < .001). Comparatively, the analysis of the mean amount of time spent in MVPA10mins showed significance in the main effect of both time periods (p = .02) and gender differences (p = .02), with the female participants recording significantly lower physical activity levels than the males. In conclusion, given these physical activity patterns of the adolescents, interventions should focus on creating weekend activities and increasing their bout duration.